Time series analysis forecasting and control - Box, George E. P.; Jenkins, Gwilym M.; Reinsel, Gregory C. (Wiley series in probability and statistics, 2008)
"A modernized new edition of one of the most trusted books on time series analysis. Since publication of the first edition in 1970, Time Series Analysis has served as one of the most influential and prominent works on the subject.